EFEKTIFITAS TEKNIK RELAKSASI NAFAS DALAM DAN DZIKIR TERAPI TERHADAP NYERI POST OP KATARAK - Yuniarti, Yuniarti; Darwin, Darwin; Huda, Nurul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The purpose of this study was to investigate the effectiveness of breath relaxation techniques and dzikir therapy to postop cataract pain. The research method used was quasy experiment with pre test design and post test design with nonequivalent control group. This research was conducted in RSUD Arifin Achmad Riau Province to 34 subjects that weredivided into two groups, namely experimental group 17 subjects and control group 17 subjects. The measuringinstrument used in both groups is a pain observation sheet with a numeric rating scale. The analysis used wasunivariate and bivariate analysis using Wilcoxon and Mann-Whitney. Wilcoxon test obtained experimental group pvalue 0.000 < α (0,05) and control group p value 0,034 < α (0,05) showed that decrease of group experiment grouppain scale bigger than control group. The independent t test result showed p value 0.000 <α (0,05), which means thatgiving deep breath relaxation technique and dzikir therapy effective to reduce patient's post cataract pain. Based on thisresearch, the provision of deep breath relaxation and dzikir therapy can be used as one of the non-pharmacologicaltechniques in reducing post-operative pain of cataract patients.Key Words : Pain, Breath Relaxation, Dzikir Therapy